Peningkatan Kemampuan Guru dalam Menyusun Perencanaan dan Melaksanakan Pembelajaran Paikem-Gembrot Melalui Model Makek Pada SD Inpres 3/77 Lanca Kabupaten Bone - Abd Rahim Rahim (Universitas Negeri Makassar, 2018)
One of the principles in KTSP is that learning must uphold the five pillars oflearning, among others, in order to give learners the opportunity to learn to believe and fearAllah Almighty, learn to live together and be useful to others, and learn to build and findteak the self through an active, innovative, creative, effective, fun, joyful and rewardinglearning process (PAIKEM-GEMBROT). PAIKEM-GEMBROT is a learning model thatenables learners to engage in diverse activities to develop skills, attitudes andunderstanding of different sources and learning aids including the use of the environmentso that learning is more interesting, fun and effective. Therefore, gurupun prosecuted to bemore active and creative .. The results showed that SD Inpres 3/77 Lanca Kab. Bone,84.21% of teachers are less well understood and have not implemented PAIKEMGEMBROT.The remaining 17, 79% have already learned about PAIKEM-GEMBROTGEMBROTand have tried it in learning. After receiving guidance and guidance throughaction in this school action research, 80.52% of Inpres 3/77 Lanca elementary schoolteachers were able to arrange the RPP with PAIKEM-GEMBROT nuance and 70.98% ofteachers of Inpres 3/77 Lanca Kab. Bone is able to implement PAIKEM-GEMBROTGEMBROT.